2020
DOI: 10.1002/lpor.202000233
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Emission of Plasmon‐Exciton Polaritons Revealed by Ultrafast Nonradiative Decays

Abstract: Spontaneous emission can be altered by external electromagnetic environment with the bridge of local density of optical states. Microcavities have been widely integrated to accelerate the irreversible spontaneous decay, known as the Purcell effect. However, the Purcell effect breaks down in the strong coupling regime, where the light‐matter interaction is not a perturbation to Fermi's golden rule. Here, it is found that the emission intensity of plasmon–exciton polaritons is asymmetrically dependent on the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Beyond excitonic nanolaser, due to the bosonic character, exciton-polariton condensation can lead to laser-like emission at much lower threshold powers than in conventional photon lasers. [201][202][203] The coupling between cavity and 2D exciton undoubtedly provides new opportunities for other researches, such as strongly coupled cavity quantum electrodynamics, [204][205][206] cavity nonlinear optics, [207][208][209] and optically quantum manipulation. [210,211]…”
Section: Excitonic Nanolasermentioning
confidence: 99%
“…Beyond excitonic nanolaser, due to the bosonic character, exciton-polariton condensation can lead to laser-like emission at much lower threshold powers than in conventional photon lasers. [201][202][203] The coupling between cavity and 2D exciton undoubtedly provides new opportunities for other researches, such as strongly coupled cavity quantum electrodynamics, [204][205][206] cavity nonlinear optics, [207][208][209] and optically quantum manipulation. [210,211]…”
Section: Excitonic Nanolasermentioning
confidence: 99%
“…Excitons in various materials, such as J -aggregates of organic dye molecules and transition metal dichalcogenides, strongly couple with the plasmon excited in metal nanostructures due to a large transition dipole moment of the exciton and a small mode volume of the plasmon. Plasmon–exciton hybrid systems have been extensively studied using various spectroscopic techniques, such as dark-field scattering, , extinction, absorption, and photoluminescence (PL). , Single-particle spectroscopy has been carried out using dark-field scattering and PL. In dark-field scattering spectroscopy, peak splitting due to the formation of coupled states is observed, and Rabi splitting is evaluated from the resonance energies of the peaks.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral properties of PL from hybrids have been extensively studied. Shan et al reported nearly no PL enhancement on a hybrid structure of a gold nanodisk with single-layer WSe 2 , 23 while Deng et al reported an over 1000-fold enhancement on a hybrid structure of a gold nanorod and single-layer WS 2 . 22 The magnitude of the enhancement is strongly dependent on the hybrid system studied, and the mechanism of the enhancement remains to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…子或量子点)激励。纳米光学天线为诸多 SPP 相关应用奠定了基础,例如光伏器 件和太阳电池 [4] 、高分辨率光刻 [5] 、超快非相干光源 [6] 、表面增强拉曼散射 [7] 、基 于荧光共振能量转移的 mRNA 探测 [8] 、SPP 和荧光辐射源的强耦合 [9,10] 、偏振依 赖的 SPP 传播方向控制 [11] 、SPP 激光器 [12] 等。 一种金属镜面上纳米颗粒(nanoparticles on mirror, NPoM)的天线结构,因 制造简单、结构参数可控、且具有极好的局域场增强效果,引起了广泛的研究兴 趣。该结构为金属基底-介质纳米间隙-金属纳米颗粒的三明治结构,纳米间隙的 尺寸可小到纳米甚至亚纳米量级,并且精确可控(例如,采用镀膜工艺制作介质 薄膜) ,其中支持间隙表面等离激元 [13] (gap surface plasmon, GSP) ,具有远低于 衍射极限的模式体积 V [14] 。当点辐射源放置于纳米间隙时,能够激励 GSP,获得 极大的自发辐射速率增强 Purcell 因子 F p (正比于 Q/V,Q 是 GSP 模式的品质因 子) [3,15,16] ,能够缩短荧光寿命,用于提升单光子源 [3,17,18] 、纳米激光器 [19] 等高速 纳米光源的调制速度。同时,GSP 引起的局域场增强能够提升辐射源的荧光激发 速率和量子产率 [20,21] ,从而提高荧光强度,可用于高亮度光源 [18,22] 、高灵敏荧光 传感 [20] 、表面增强拉曼散射等 [7,23] 。 不同于仅支持局域等离激元共振(localized surface plasmon resonance, LSPR) 的单个纳米光学天线 [3,14,24] , 纳米天线周期阵列能够同时支持 LSPR 和表面晶格共 振(surface lattice resonance, SLR) [25][26][27][28][29] 。其中,LSPR 能够实现阵列中单个天线 位置的电磁场增强和自发辐射增强 [3] ,SLR 来自阵列中各天线散射场的相长干涉 叠加,能够实现沿特定方向的远场定向辐射 [25][26][27][28] 。上述两种物理性质使纳米天线 周期阵列能够实现大面积的电磁场增强和自发辐射增强以及远场定向辐射,可应 用于高效率光伏器件 [30,31] 、定向辐射固态光照明器件 [22,32] 等。 对于单个点辐射源激励下纳米天线周期阵列的设计,单个点源破坏了电磁场 3 的周期性,使得电磁场无法直接计...…”
unclassified